2019
DOI: 10.3390/su11164273
|View full text |Cite
|
Sign up to set email alerts
|

What is the Development Capacity for Provision of Ecosystem Services in the Czech Republic?

Abstract: The aim of our study is to identify the evolution of land use and the landscape capacity to provide selected ecosystem services (ESs) over the past 28 years. The results obtained should answer whether the recorded land cover development has manifested in the same way as the development of landscape capacity to provide ESs for four different services. Corine Land Cover (CLC) data are used to describe the land cover for five time periods (1990, 2000, 2006, 2012, and 2018) for the area of interest—the whole of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This is likely to be most effective in production sectors that have a high energy intensity and already have exhausted many options for easy energy intensity improvements. In those sectors related to land-use change, such as agriculture or forestry, another important objective for the post-growth economy would be to restore the capacity of the land to provide important ecosystem services [66].…”
Section: Potential Energy Savings From Structural Changementioning
confidence: 99%
“…This is likely to be most effective in production sectors that have a high energy intensity and already have exhausted many options for easy energy intensity improvements. In those sectors related to land-use change, such as agriculture or forestry, another important objective for the post-growth economy would be to restore the capacity of the land to provide important ecosystem services [66].…”
Section: Potential Energy Savings From Structural Changementioning
confidence: 99%
“…At the highest level, the area of interest was the entire country (the Czech Republic). A description of the natural conditions in the country was given by Pechanec et al [91]. The Dřevnice catchment area is located in the southeastern part of the Czech Republic (Figure 2), and the Všemina catchment area is located in the northwestern part of the Dřevnice River basin.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies on the evolution of land use and the ability of landscapes to provide selected ecosystem services (ESs) have found that the assessed areas have the greatest capacity to provide ecological integrity, which decreases slightly due to category changes. In addition, it has been verified that ecological integrity and regulation services have similar development characteristics [2]. Researchers have applied the concept of project evaluation system (PES) to the monetary valuation of natural forest habitats and created the Natura 2000 European network.…”
Section: Introductionmentioning
confidence: 99%